Clinical Cases in Skin Cancer Surgery and Treatment - Paul, Sharad P.; Norman, Robert A. (Clinical Cases in Dermatology, 2016)
This clinical case book serves as a useful guide for dermatologists, surgeons, family practitioners, residents and anyone who is engaged in the practice of cutaneous surgery to manage skin cancer. The case-study-based format allows readers to understand planning of procedures and surgical techniques, and the differing cases are designed to relate to different situations that may arise within dermatosurgery practices. Clinical Cases in Skin Cancer Surgery and Treatment provides relevant surgical and anatomical tips, and finer points of surgical techniques gleaned from the author's experience. Each chapter covers a different type of case, flap or skin graft closure, and will help the attending physician or surgeon in improving their skill levels and knowledge. The Editors and contributors provide enough detail to allow residents or family practitioners to develop further competence in the surgical management of skin cancers, while ensure that this book serves as a useful practical guide. For more experienced cutaneous surgeons, the book helps in fine-tuning techniques and reinforcing good practice methods.